2021
DOI: 10.1186/s13287-021-02301-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Spanish population coverage of a prospective HLA haplobank of induced pluripotent stem cells

Abstract: Background iPSC (induced pluripotent stem cells) banks of iPSC lines with homozygous HLA (human leukocyte antigen) haplotypes (haplobanks) are proposed as an affordable and off-the-shelf approach to allogeneic transplantation of iPSC derived cell therapies. Cord blood banks offer an extensive source of HLA-typed cells suitable for reprogramming to iPSC. Several initiatives worldwide have been undertaken to create national and international iPSC haplobanks that match a significant part of a popu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Development of an HLA homozygous iPSC bank in countries with high HLA variability may require more time and money to achieve wider coverage. For instance, 631 HLA homozygous iPSCs would be required to cover 90% of the Spanish population, while less than 200 iPSCs are required to reach the same coverage in Korea [ 111 ]. Reducing the required number of matching HLA alleles may help to reduce the number of iPSC lines required to cover most of the population in countries with high HLA variability.…”
Section: Ipsc-based Cell Therapymentioning
confidence: 99%
“…Development of an HLA homozygous iPSC bank in countries with high HLA variability may require more time and money to achieve wider coverage. For instance, 631 HLA homozygous iPSCs would be required to cover 90% of the Spanish population, while less than 200 iPSCs are required to reach the same coverage in Korea [ 111 ]. Reducing the required number of matching HLA alleles may help to reduce the number of iPSC lines required to cover most of the population in countries with high HLA variability.…”
Section: Ipsc-based Cell Therapymentioning
confidence: 99%
“…The whole Spanish cord blood registry comprises 52,220 donations. From the 9419 which are genotyped in high resolution, we identified 109 homozygous units corresponding to 43 different haplotypes and we ranked the haplotypes priority according to the cumulative coverage capacity for HLA matching, as previously described [12]. The average pre-freeze content in CD34+ in the homozygous units was 5.51 × 10 6 .…”
Section: Cbu Selection Criteriamentioning
confidence: 99%
“…This approach has shown promising results in primates [10]. Since HLA haplotypes differ in each geographical area, several studies have identified the most common haplotypes that would serve a national or regional population and calculated the number of HLA homozygous iPSC lines (haplolines) to cover a significant percentage [9,11,12]. Cord blood banks provide an excellent source of starting material for the production of iPSC: the samples are banked in great numbers, they are already HLA-typed and screened for the presence of virus and pathologies [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These lines can be subject to regulatory clearance via vigorous tests on their genome stability, viral contamination, differentiation capability, and tumorigenicity [ 149 , 150 ]. Thus, the idea of haplobanking of HLA-homozygous iPSCs was spawned [ 152 , 153 , 154 ]. Notably, the first clinical trial led by Dr. Masayo Takahashi used autologous iPSC for treating neovascular age-related macular degeneration (AMD).…”
Section: The Ipsc-based Disease Modelling and Ipsc Therapy In Clinical Trialsmentioning
confidence: 99%